2011
DOI: 10.5194/hess-15-57-2011
|View full text |Cite
|
Sign up to set email alerts
|

A summer climate regime over Europe modulated by the North Atlantic Oscillation

Abstract: Abstract. Recent summer heat waves in Europe were found to be preceded by precipitation deficits in winter. Numerical studies suggest that these phenomena are dynamically linked by land-atmosphere interactions. However, there exists as yet no complete observational evidence that connects summer climate variability to winter precipitation and the relevant circulation patterns. In this paper, we investigate the functional responses of summer mean and maximum temperature (June-August, T mean and T max ) as well a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…By comparing regional climate simulations of a coupled atmosphereland-surface model scheme to an uncoupled model scheme for selected summer heat waves in Europe, Fischer et al (2007) estimated that land-atmosphere interactions over dry areas increase the number of heat days by 50-80 %. Wang et al (2011) supported the findings of Fischer et al (2007) by analysing observational data of the Mediterranean region. Zampieri and D'Andrea (2009) found that spring droughts in the Mediterranean favor the development of strong heat events in "temperate continental Europe", and Hirschi et al (2011) point out the importance of soil-moisture deficit for the development of strong heat waves in southeastern Europe.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…By comparing regional climate simulations of a coupled atmosphereland-surface model scheme to an uncoupled model scheme for selected summer heat waves in Europe, Fischer et al (2007) estimated that land-atmosphere interactions over dry areas increase the number of heat days by 50-80 %. Wang et al (2011) supported the findings of Fischer et al (2007) by analysing observational data of the Mediterranean region. Zampieri and D'Andrea (2009) found that spring droughts in the Mediterranean favor the development of strong heat events in "temperate continental Europe", and Hirschi et al (2011) point out the importance of soil-moisture deficit for the development of strong heat waves in southeastern Europe.…”
Section: Discussionsupporting
confidence: 66%
“…For example Hirschi et al (2011) found that drier surface conditions lead to an intensification of hot extremes in southeastern Europe; Barriopedro et al (2011) came to similar conclusions for the hot summer of 2010 in western Russia, and Wang et al (2011) found similar relationships in the Mediterranean. A first attempt to check if the results are valid for a larger area is made, by applying the methods described to the region 30 • N-70 • N, −20 • E-70 • E (not shown).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The analysis method is based on the coupled manifold (CM) technique (Navarra and Tribbia, 2005), which was specifically designed to analyse covariation between fields considering both the local and remote forcing of one field to the other. The CM technique has proved to be successful for the analysis of different climate fields, like precipitation, vegetation characteristics, sea surface temperature (SST), and temperature over land (Alessandri and Navarra, 2008;Cherchi et al, 2007;Wang et al, 2011a). Recently, the CM technique has been also applied to investigate the relationship between surface temperature and electricity demand in summer (De Felice et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The climate over Europe is related mainly to the North Atlantic sector, which is ordinarily captured by the North Atlantic Oscillation (NAO) (Hurrell, 1995). Thorough research has been conducted relating the NAO to temperatures (Pozo-Vázquez et al, 2001;Wang et al, 2011), precipitation (Uvo, 2003;Bartolini et al, 2009) or directly to discharges (Shorthouse and Arnell, 1999;Rimbu et al, 2002). Pekárová and Pekár (2007) recently investigated teleconnections of streamflow fluctuations in Slovakia with Quasi-Biennial Oscillation (QBO), Southern Oscillation (SO), NAO, and Arctic Oscillation (AO).…”
Section: Introductionmentioning
confidence: 99%